SUMOylation Wrestles With the Occurrence and Development of Breast Cancer - Qin, Yuanyuan; Yuan, Hong; Chen, Xu; Yang, Xinyi; Xing, Zhengcao; Shen, Yajie; Dong, Wanying; An, Siming; Qi, Yitao; Wu, Hongmei (Frontiers in Oncology, 2021)
Breast cancer has the highest incidence among cancers and is the most frequent cause of death in women worldwide. The detailed mechanism of the pathogenesis of breast cancer has not been fully elucidated, and there remains a lack of effective treatment methods for the disease. SUMOylation covalently conjugates a large amount of cellular proteins, and affects their cellular localization and biological activity to participate in numerous cellular processes. SUMOylation is an important process and imbalance of SUMOylation results in the progression of human diseases. Increasing evidence shows that numerous SUMOylated proteins are involved in the occurrence and development of breast cancer. This review summarizes a series of studies on protein SUMOylation in breast cancer in recent years. The study of SUMOylated proteins provides a comprehensive understanding of the pathophysiology of breast cancer and provides evolving therapeutic strategies for the treatment of breast cancer.